Headaches - Kittredge, Mary, 1949- (New York : Chelsea House Publishers, 1989)
Discusses headaches--causes, treatments, and various kinds.
Includes bibliographical references.
Booklist.
Wilson's Junior High School.
Wilson's Senior High School.
7.8
7-9
Keywords: Headache -- Juvenile literature; Headache; Headache